Penerapan Pembelajaran STEAM dalam Meningkatkan Kecakapan Peserta Didik MI Wahid Hasyim Yogyakarta - Himmatin Nur Fadila; Alma Pratiwi Husain (STKIP Andi Matappa Pangkep, 2023)
This study aims to describe the application of the STEAM learning model to improving the skills of elementary school students in the city of Yogyakarta. This study uses a narrative method with interview techniques. The research subject was a class IV teacher at MI Wahid Hasyim Yogyakarta. The results of the study show that the application of the STEAM learning model can be used to improve literacy skills at the elementary school level. This literacy skill is important to have to help with critical thinking, creative thinking, being able to solve problems, and having good communication skills. This STEAM learning model also provides an atmosphere that is in accordance with real life in the learning activities carried out, making it easier for students to reason and be active while in the classroom. The application of the STEAM model is carried out with planning that is adjusted to the curriculum and characteristics of students; in practice, each topic is discussed according to the science component of the STEAM model, and the assessment is carried out in accordance with STEAM learning objectives, namely making learning more meaningful by collaborating material with real life.